2014
DOI: 10.1111/ejss.12209
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling labile soil organic matter vulnerability to loss following disturbance as assessed by measurement of soil‐respired δ13CO2

Abstract: Summary Labile soil organic matter (SOM) is often stabilized in soil, but is vulnerable to loss after soil disturbance. We used measurements of the 13carbon (13C) signature of soil‐respired CO2 (δ13CO2) immediately after the disturbance caused by coring and sampling the soil, to assess labile SOM availability and potential vulnerability to loss. We incubated a range of pasture soils over 300 minutes and periodically measured δ13CO2. Strong temporal trends in δ13CO2 suggest that labile SOM became vulnerable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
(63 reference statements)
1
12
1
Order By: Relevance
“…In previous studies, soil LOC was mostly measured by physical or chemical extractions, which is not all available to soil organisms (Zakharova et al 2015, Moinet et al 2018. The physical and chemical fractions of SOC were not appropriate early indicators for carbon stock changes (Leifeld and K€ ogel-Knabner 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, soil LOC was mostly measured by physical or chemical extractions, which is not all available to soil organisms (Zakharova et al 2015, Moinet et al 2018. The physical and chemical fractions of SOC were not appropriate early indicators for carbon stock changes (Leifeld and K€ ogel-Knabner 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Dungait et al (2012) showed that the losses of soil organic carbon is regulated by microbial accessibility to soil organic matter and this is related closely to soil physical structure (Six et al, 2002). This structure can be modified by soil physical disturbance such as sieving (Zakharova et al, 2014(Zakharova et al, , 2015. This suggests that attempts to partition R H from R S needs to be done in intact, undisturbed systems.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the amount of labile organic C and N, which are readily decomposable by soil microorganisms according to Zsolnay (1996) and Zakharova et al . (2015) were determined in the form of cold water‐extractable C (CWC) and N (CWN) as described in Schmidt et al . (2017).…”
Section: Methodsmentioning
confidence: 99%
“…To determine the potentially bioavailable soil organic C and N for microbial utilization, hot water extractable C and N (HWC and HWN respectively) were measured (Ghani et al, 2003;Schulz et al, 2011;Francioli et al, 2016). Additionally, the amount of labile organic C and N, which are readily decomposable by soil microorganisms according to Zsolnay (1996) and Zakharova et al (2015) were determined in the form of cold water-extractable C (CWC) and N (CWN) as described in Schmidt et al (2017) (Gardes and Bruns, 1993;Leonhardt et al, 2019)/P7-3N-fITS7 + P7-4N-fITS7 (Ihrmark et al, 2012;Leonhardt et al, 2019) were used to amplify fungal ITS2 rDNA, with the Illumina adapter sequences in all the primers. We used the proofreading KAPA Hifi polymerase (Kapa Biosystems, Boston, MA, USA) in all the PCR reactions.…”
Section: Physico-chemical Analyses Of the Soil Samplesmentioning
confidence: 99%